Assessing the Bolted Connection Strength of New Zealand Hardwood - Abdul Razak, Abdul Karim; Quenneville, Pierre; Norazzlina, M.Sa‘don; Ingham, Jason M. (New Zealand Society for Earthquake Engineering, 2010)
From published literature, it was found that through-bolt connections were typically applied as a retrofit technique to most New Zealand unreinforced masonry (URM) buildings following the 1931 Hawke’s Bay earthquake. As connection failure by tearing out part of the diaphragm joist was observed in past earthquakes due to lateral earthquake loading, the strength of the bolted connection in existing indigenous New Zealand timber joists needs to be assessed. The main objectives of this study were to evaluate the strength and to identify the possible failure modes of bolted connections in New Zealand hardwood. Bolted connection tests loaded parallel-to-grain were performed using recycled native New Zealand Matai and Rimu hardwoods because the timber diaphragms in URM buildings are typically constructed using such wood species. From the experimental study, it was observed that the timber bolted connection can fail in either ductile or brittle modes. The test results obtained were compared with the European Yield Model (EYM), the New Zealand timber code (NZS 3603:1993), and a proposed set of equations (Quenneville 2009) in order to evaluate the applicability of those equations in predicting bolted connection strength for New Zealand hardwood. It was found that the EYM equations provide better predictions than the NZS 3603:1993 when compared to the actual capacity. However, the EYM predictions are only good in estimating the strength of timber bolted connections that fail under ductile mode. For the connections that fail exhibiting the brittle mode, the proposed row shear equation by Quenneville was found to give better strength estimation.